TINGKAT KEPUASAN PENGUNJUNG PUSKESMAS DI KOTA YOGYAKARTA: Studi Berdasarkan Review Google Maps - Ary Sutrichastini; Priyastiwi; Agung Jaya Indarto; Sofiati; Linawati; Yenni Kurnia Gusti (Jurnal Riset Manajemen Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha Program Magister Manajemen, 2023)
Google Maps is an application that is used to find locations, reviews of services and conditions of the desired location. Likewise, to find out the Puskesmas services can be seen on Google Maps, but the Google Maps review has not been used as a basis for improving health services at the Puskesmas. The purpose of this study was to measure the satisfaction level of visitors to the Puskesmas in the Yogyakarta City based on the Google Maps rating value and to identify the factors that cause satisfaction and disappointment of visitors to the services of the Puskesmas in the city of Yogyakarta. The research method uses a visitor survey at 18 Puskesmas in Yogyakarta City was 1,096 respondents. The results obtained are the average rating of the satisfaction level of Puskesmas visitors in the Yogyakarta City of 3.87. The factors that make visitors feel satisfied with the services of the Puskesmas in Yogyakarta City are friendly service and officers by 29.2%, strategically comfortable places and complete facilities by 10.4%, orderly queues (3.3%). While the factors that disappointed visitors were 112 statements (10.5%) which stated slow service, long queues (5.05%), unfriendly staff (2.9%) and narrow waiting rooms and parking spaces (3. 2%). The research results can be used by Puskesmas managers in improving the services provided.